Vienna - Clarke, W.B. (William), 1809-1889 (architect):::Creator:::::::::::: (United Kingdom; London; Chapman and Hall)
Map of Vienna, including the inner city and surrounding suburbs, with graphics of various buildings of Vienna at foot and a scale of distances.